Differential effects of carvedilol and atenolol on plasma noradrenaline during exercise in humans - Herman, R.B.; Jesudason, P.J.; Mustafa, A.M.; Husain, R.; Choy, A.M.J.; Lang, C.C. (2003)
Aims Evidence of long-term beneficial effects of beta-blockers on mortality and morbidity in patients with heart failure has been demonstrated in recent randomized trials. However, not all beta-blockers are identical. Carvedilol, a nonselective beta- and alpha-adrenergic blocker, can potentially blunt the release of noradrenaline by blocking presynaptic beta(2)-adrenergic receptors. To test this hypothesis, we have compared the effects of carvedilol and atenolol on plasma noradrenaline during exercise in healthy young volunteers. Methods This study investigated the differential effects of 2 weeks pretreatment with carvedilol 25 mg day(-1) and atenolol 50 mg day(-1) on plasma noradrenaline at rest and during exercise on a treadmill in a double-blind randomized crossover study, involving 12 healthy male volunteers (mean age 21.6 +/- 0.3 years). Results Haemodynamic parameters at rest and during exercise were not significantly different in either carvedilol or atenolol pretreatment groups. However, carvedilol pretreatment significantly blunted the increase in plasma noradrenaline during exercise 393.8 +/- 51.7 pg ml(-1) (pretreatment) to 259.7 +/- 21.2 pg ml(-1) (post-treatment), when compared with atenolol 340.4 +/- 54.6 pg ml(-1) (pretreatment) to 396.2 +/- 32.0 pg ml(-1) (post-treatment). The difference between carvedilol and atenolol (95% confidence interval) was -145.2, -351.0, P < 0.05. Conclusions We have demonstrated that carvedilol but not atenolol significantly blunted the increase in plasma noradrenaline during exercise. These findings may suggest a sympathoinhibitory effect of carvedilol that may enhance its ability to attenuate the cardiotoxicity associated with adrenergic stimulation in patients with heart failure.